2015
DOI: 10.1111/bjep.12095
|View full text |Cite
|
Sign up to set email alerts
|

The gender gap in student engagement: The role of teachers’ autonomy support, structure, and involvement

Abstract: Although involvement and autonomy support partly explained the gender gap in engagement (mediation hypothesis), more support was found for differential effects of autonomy support on boys' versus girls' engagement (differential effects hypothesis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
102
5
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(134 citation statements)
references
References 68 publications
18
102
5
9
Order By: Relevance
“…This result is consistent with past findings that course engagement was significantly higher for male learners in MOOCs (Williams et al, 2018). However, this finding contradicts many studies reporting that female students had higher engagement levels than male students in traditional school settings (Fullarton, 2002; Lietaert, Roorda, Laevers, Verschueren, & De Fraine, 2015; Wang et al, 2011) and university settings (Kinzie et al, 2007; Kuh, 2003; Sontam & Gabriel, 2012). Future research could further explore the differences in gender‐engagement relationships between technology‐enhanced learning environments and traditional education settings.…”
Section: Discussionmentioning
confidence: 75%
“…This result is consistent with past findings that course engagement was significantly higher for male learners in MOOCs (Williams et al, 2018). However, this finding contradicts many studies reporting that female students had higher engagement levels than male students in traditional school settings (Fullarton, 2002; Lietaert, Roorda, Laevers, Verschueren, & De Fraine, 2015; Wang et al, 2011) and university settings (Kinzie et al, 2007; Kuh, 2003; Sontam & Gabriel, 2012). Future research could further explore the differences in gender‐engagement relationships between technology‐enhanced learning environments and traditional education settings.…”
Section: Discussionmentioning
confidence: 75%
“…In the present sample, a gender difference was found with regard to boys’ higher ratings of disaffection and help‐seeking and their lower ratings of behavioural/cognitive engagement. The interaction effect, which was found for gender, indicated that emotional support in the classroom predicted students’ emotional engagement differently for girls and boys: girls seemed to benefit more than boys from emotional support in teacher–student interactions with respect to their situational experience of emotional engagement (cf., Roorda et al ., ; see also Lietaert, Roorda, Laevers, Verchueren, & De Fraine, ). The reasons behind this gender difference cannot be inferred based on the present data.…”
Section: Discussionmentioning
confidence: 96%
“…For example, previous research pointed to considerable gender differences, with girls typically reporting higher engagement than boys (e.g. Lietaert et al , 2015). Other studies demonstrated that the levels of engagement change with age, generally decreasing during secondary school (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%